Effects of Phytase, Phosphorus, Protein and Temperature on Growth, Apparent Nutrient Digestibility and Carcass Characteristics of Broiler Chickens - Lai, Pui Wah (2005)
Feeding excessive dietary phosphorus (P) is not only expensive but would lead to environmental pollution and mineral binding. Phytase has been utilized extensively to break down the links between nutrients and the phytate ring, increasing nutrients availability, thus creating both economic and environmental advantages. High temperatures are detrimental to poultry performance. Since sophisticated cooling systems are costly, dietary protein manipulation is one of the corrective approaches to overcome the adverse effects of heat stress. The objectives of the present study were to investigate the effects of phytase, inorganic P, crude protein (CP), environmental temperature (T) and their two-way interactions on growth performance, apparent nutrient digestibility and carcass characteristics in broiler chickens. Phytase supplementation by itself did not affect (P>0.05) the broilers' growth performance; bone, carcass characteristics, meat tenderness and water holding capacity. However, addition of P enhanced the birds' appetite, improved (P<0.05) FI, BWG and FCR. Increasing dietary CP decreased feed intake (FI) but enhanced iii (P<0.05) body weight gain (BWG) and feed conversion ratio (FCR). Broilers in the lower T chamber had better growth rate than those in the warmer environment. Broilers given supplemental phytase and 23% CP diet performed better than their counterparts. Addition of P ameliorated the adverse effects of low dietary CP content or high T, indicating a significant (P<0.05) interaction. Increasing dietary CP content did not impair the growth performance of the broilers in the higher T chamber as reported probably because the elevation of T was not high enough to cause hyperthermia. Phytase increased (P<0.05) the apparent digestibility of calcium (Ca) suggesting a higher release of Ca from the phytate mineral complex. As the dietary P level increased, apparent digestibilities for apparent metabolizable energy (AME) was decreased Ca, P and CP were increased (P<0.05). Apparent digestibility for P increased (P<0.05) but was vice versa for Ca as CP level increased. Elevating the environmental T reduced (Pc0.05) the apparent digestibility for Ca and CP but increased (Pc0.05) apparent P digestibility. Phytase x P effect was significant (PC0.05) on the apparent digestibility for Ca. Supplemental phytase with 23% dietary CP increased the apparent digestibility for P, indicating phytase and CP interaction (W0.05). Birds fed with supplemental P and 23% CP diet utilized the P and CP more efficiently. Warm condition restored the deleterious effect of non supplemental P diets for P utilization. Bone development improved (P<0.05) when P was added. Ash content was not affected (P>0.05) by dietary CP content while better (P<0.05) bone mineralization was observed from the birds in the lower T environment. P x CP interaction (P<0.05) was noted on the bone strength, with increasing dietary P and CP levels effecting improved bone stren@ Birds supplemented with P and kept in the cooler environment had stronger tibia than other b i i in dicating P x T effect (P<0.05). Supplemental phytase increased (P-4.05) serum P level and reduced alkaline phosphatase (ALKP) level. P deficiency resulted in increment in serum Ca and a decrease in serum P levels. An increased serum ALKP activity noted was in r e s p g ~ to decreasing P level or CP content in the did Phytase x P effect was significant (P<0.05) on serum P and ALKP level. Phytase ameliorated the negative effect of low dietary CP level on the P availability. Birds fed supplemental P and 23% CP diet had .- higher serum P and lower ALKP level. Additional P and higher CP content in the diet restored the detrimental effects of high T on P utilization in broilers. Supplemental P increased (P<0.05) carcass yield while 23% CP diet improved carcass characteristics and caused a reduction (PK0.05) in leaf fat. Broilers in the lower T environment had better carcass characteristics. Addition of phytase restored the low protein effect to increase leaf fat. For birds fed with supplemental P in the 23% CP diet, better carcass characteristics were observed, indicating P x CP effect (K0.05). Birds kept in the lower T chamber and provided with P or 23% CP feed had heavier carcass components. Broilers fed higher CP (23%) diet had tougher breast meat than those fed lower CP feed while more tender breast meat was obtained fiom the b i i kept in the lower T chamber as compared to those kept in the higher T. WHC of the meat was affected by dietary P, CP and environmental T.